The foreigner - Campbell, Martin; Marconi, David; Chan, Jackie, 1954-; Godfrey, Wayne Marc, 1981-; Sarkissian, Arthur; Qi, Jianhong (Producer); Kupchak, Claire, 1968-; Zeng, John; Lumpkin, D. Scott; Marshall, Jamie (Producer); Schulman, Cathy; Brosnan, Pierce; et al. (Universal City, CA : Universal Pictures Home Entertainment, 2018)
A humble businessman with a buried past seeks justice when his daughter is killed in an act of terrorism. A cat and mouse conflict ensues with a government official, whose past may hold clues to the killers' identities.
Originally produced as a motion picture in 2017.
Based on the novel The Chinaman / by Stephen Leather.
Wide screen (2.40:1).
Bonus materials: The making of The foreigner; interviews; trailers.
Director of photography, David Tatterssall ; editor, Angela M. Catanzaro ; music, Cliff Martinez.
Jackie Chan, Pierce Brosnan, Orla Brady, Dermot Crowley, Ray Fearon, Rory Fleck Byrne, Michael McElhatton, Charlie Murphy, Liu Tao, Lia Williams.
Keywords: Fathers and daughters -- Drama; Terrorism -- Drama; Revenge -- Drama